O problema da demarcação e o estatuto das "leis naturais" em Karl Popper - Clifford Patrick Tavares Hodgson (2003)
This dissertation aims at studying the problem of demarcation inPopper, specially in those aspects that refer to the characterization of thescientific statements of unrestricted universality in opposition to theirsimilar pseudo-scientific or metaphysical statements. We initially focused on the contrast between the methodological approach of Popper and the syntactical-semantic approach of logical positivism. Starting, then, from the development of the popperian approach, we examine some of its possible consequences through a text of Antonio J. Diéguez, which is inspired in the criticism of Thomas Kuhn and Imre Lakatos of Popper's demarcation criterion. We got finally to the conclusion that Diéguez's criticism of the popperian criterion does not sustain itself when a more accurate description of Popper's thought is made.